2015
DOI: 10.1080/09658211.2015.1071852
|View full text |Cite
|
Sign up to set email alerts
|

The crutch of context-dependency: Effects of contextual support and constancy on acquisition and retention

Abstract: Paired associates (Tagalog-English word pairs) were studied and practiced with pairs superimposed over pictorial contexts, and tested with no context cues. On every retrieval practice (RP) incidental or conceptually supportive contexts were repeatedly shown with the same pair (constant context condition), or else new contexts were shown on every RP trial (varied context condition). Incidental contexts in the constant condition and supportive contexts in both constant and varied context conditions facilitated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 13 publications
1
60
2
1
Order By: Relevance
“…Previous research has shown that cued recall, using paired associates, is susceptible to the types of context manipulations that we used in the present experiments (e.g., Smith et al, 2014;Smith & Handy, 2014. Smith et al (2014), for example, observed context-dependent cued recall using Swahili-English word pairs, Smith and Handy (2014) found the effect using face-name pairs, and Smith and Handy (2016) found it using Tagalog-English word pairs. The word pairs used in Experiment 1 of the present study, however, differed from previously reported methods because the two words of our pairs were in the same language, semantically related to each other (e.g., COTTAGE-hut, SWISS-chocolate, CAKEicing).…”
Section: Discussionmentioning
confidence: 63%
“…Previous research has shown that cued recall, using paired associates, is susceptible to the types of context manipulations that we used in the present experiments (e.g., Smith et al, 2014;Smith & Handy, 2014. Smith et al (2014), for example, observed context-dependent cued recall using Swahili-English word pairs, Smith and Handy (2014) found the effect using face-name pairs, and Smith and Handy (2016) found it using Tagalog-English word pairs. The word pairs used in Experiment 1 of the present study, however, differed from previously reported methods because the two words of our pairs were in the same language, semantically related to each other (e.g., COTTAGE-hut, SWISS-chocolate, CAKEicing).…”
Section: Discussionmentioning
confidence: 63%
“…Supporting evidence comes from Smith and Handy (2014), which in three out of four experiments found a benefit of testing with feedback in varied digital contexts versus the same context when a final test occurred in a neutral context. Multiple practice test trials with feedback may also be necessary for a benefit of varied versus same-context conditions to manifest (as was observed in Smith & Handy, 2016, for the case of five vs fewer repetitions; see also Schwoebel et al, 2018, for another case of repeated testing with feedback). A further consideration is the interval between initial study and retrieval practice.…”
Section: Discussionmentioning
confidence: 97%
“…This seems intuitive because more study opportunities in the varied-encoding condition mean more ways in which memory representation is elaborated. In this regard, it is worth noting the recent contextual variability results by Smith and Handy (2016). Participants studied Tagalog–English pairs superimposed over context photographs and later completed between one and five cycles of retrieval practice (with feedback) for those pairs with either original or varied contexts.…”
Section: Discussionmentioning
confidence: 99%